Development of Second Language French Oral Skills in an Instructed Setting: A Focus on Speech Ratings - Trofimovich, Pavel; Kennedy, Sara; Blanchet, Josée (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2017)
This study examined the relationship between targeted pronunciation instruction in French as a second language (L2) and listener-based ratings of accent, comprehensibility, and fluency. The ratings by 20 French listeners evaluating the speech of 30 adult L2 French learners enrolled in a 15-week listening and speaking course targeting segments, prosody, fluency, and connected speech processes (e.g., liaison, enchainment) were compared before and after instruction in read-aloud and extemporaneous (picture description) speaking tasks. Results showed that the learners improved in all speech ratings, especially in extemporaneous speaking. Results also revealed that accent ratings were linked to prosody (intonation accuracy, pitch range), while fluency and comprehensibility ratings were additionally linked to fluency phenomena (length of fluent run, hesitation rate). These findings are discussed in terms of their implications for L2 pronunciation learning and links between instruction, listener-rated dimensions of speech, and performance in different tasks.